1923 Fla. Laws 431-32, An Act for the Protection of Person Who Use Shot-guns in the Pursuit of Game and for Sport . . ., ch. 9340, § 1 - (:unkn) unknown (General Publisher, 1923)
Prohibited the sale of any shot gun shells, divested of their interstate character, which do not plainly print on the box the character, quality, and quantity of powder contained in such shells.
--
Keywords: TRANSFER ONLY